RESPON PERTUMBUHAN DAN HASIL TIGA VARIETAS KEDELAI (Glycine max, L.) TERHADAP CEKAMAN KEKERINGAN - Syamsul Bahri (Jurnal Penelitian Agrosamudra, 2017)
This study was conducted to determine the growth response and yield of three soybean varieties (Glycine max, L.) "against drought stress and interaction. This research was conducted in Birem Rayeuk, Kabupaten Aceh Timur with height of place 3 meter from sea level and soil pH 5,5. Implementation of research start from February until June 2017. This research use Randomized Block Design (RAK) with factorial pattern consisting of 2 (two) factors, namely: Factor three varieties are: V1 = Agromulyo, V2 = Wilis and V3 = Kaba and drought stress factors are: K1 = 80% of KL = 1.3 l, K2 = 60% of KL = 0.97 l, K3 = 40% of KL = 0.65 l and K4 = 20% of KL = 0.32 l. To illustrate the growth and production of soybean crops, observations were made on the parameters of plant height, number of productive branches, root length, number of pods per polybag, number of pods, dry seed weight per polybag and 100 grains of dry beans. The results showed that the treatment of three varieties had a very significant effect on plant height at age 50 HST and number of pods per polibag and significantly effect on plant height at age 35 HST. The best varieties are found in V1 treatment (Agromulyo). the drought stress treatment had a very significant effect on plant height at age 35 and 50 HST, root length, number of pods and weight of 100 grains of dried beans and significantly affect the number of productive branches and the weight of dry beans per polybag. The best growth and production of soybean due to drought stress was found in the treatment of K2 (0.97 l). The interaction between three varieties and drought stress had no significant effect on all parameters tested. In relation to the results of this study for the cultivation of soybean crops it is advisable to use Agromulyo varity and drought stress levels of 60% of KL = 0.97 l performed separately.